Effect of a water spray system on the presence of Salmonella and Listeria monocytogenes on conveyor belts in chicken slaughterhouses - Viana, Cibeli; Soares, Vanessa Mendonca [UNESP]; Pereira, Juliano Goncalves [UNESP]; Tadielo, Leonardo Ereno; Nero, Luis Augusto; Almeida Nogueira Pinto, Jose Paes de [UNESP]; Bersot, Luciano dos Santos (Elsevier B.V., 2020)
This study aimed to evaluate the effectiveness of a water spray system in cleaning conveyor belts contaminated with Salmonella and Listeria monocytogenes. Samples were obtained from modular and smooth conveyor belts from four slaughterhouses in Brazil, and bacterial presence was assessed in sprayed and unsprayed belts. From each conveyor belt, 400 cm(2) were sampled using sponges at various time periods (T-0: 5:00 h; T-1: 9:00 h; T-2 : 17:00 h, and T-3: 22:00 h), and these samples were submitted for Salmonella and L. monocytogenes detection. The results were expressed as frequencies and analyzed by Chi-square test. A low frequency of Salmonella isolation occurred at T-0, and at T-1, and T-2, the isolation frequencies of Salmonella were higher in the unsprayed conveyor belts. Salmonella contamination throughout the process fluctuated significantly (P < 0.05), and fluctuation occurred regardless of water spray use. In regard to the effect of water spraying on the presence of L. monocytogenes, the isolation frequencies were lower (P < 0.05) at all time points when the water spray system was active. Given this, our findings indicate that although water spray hygiene influences the frequency of pathogen isolation, other factors require monitoring to control for Salmonella and L. monocytogenes contamination.
Keywords: Chicken; Contamination; Pathogens; Slaughtering